Paul Samuelson's Historiography: More Wag Than Whig - E. Roy Weintraub (Duke University, Center for the History of Political Economy (CHOPE), 2015)
In this review essay of Medema's and Waterman's collection of some of Samuelson's writings in the history of economics, the author argues that Samuelson's claim to have written "Whig History" is spurious. Moreover the author argues that Samuelson's own writings on modern economics are , whether explicit or not, profoundly autobiographical. Samuelson, in constructing a literature ostensibly about c ontemporary economics, was simultaneously constructing a literature in which he and contemporary economics could be jointly considered and appraised.
Keywords: B2; D5; 330; Paul A. Samuelson; historiography; Whig History; aut obiography; history of economics